2024
DOI: 10.1039/d3tc04362b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of substituent position on crystal structure and photoconductivity in 1D and 2D lead(ii) benzenethiolate coordination polymers

Ryohei Akiyoshi,
Akinori Saeki,
Kazuyoshi Ogasawara
et al.

Abstract: Coordination polymers containing a sulfur coordination atom (S-CPs) are an emerging class of materials with unique optoelectronic properties resulting from their inorganic metal–sulfur (–M–S–)n networks. Although the structural dimensionalities of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…37 The φΣμ max value of CP1 (2.7 × 10 −5 cm 2 V −1 s −1 ) is similar to that of [Pb(ortho-SPhOMe) 2 ] n (2.5 × 10 −5 cm 2 V −1 s −1 ). 37 The low photoconductivity is related to their similar 1D (−Pb−S−) n chain dimension. These results again highlight the influence of the (−Pb−S−) n dimension on the charge mobility of Pb-based S-CP materials.…”
Section: Inorganic Chemistrysupporting
confidence: 52%
See 3 more Smart Citations
“…37 The φΣμ max value of CP1 (2.7 × 10 −5 cm 2 V −1 s −1 ) is similar to that of [Pb(ortho-SPhOMe) 2 ] n (2.5 × 10 −5 cm 2 V −1 s −1 ). 37 The low photoconductivity is related to their similar 1D (−Pb−S−) n chain dimension. These results again highlight the influence of the (−Pb−S−) n dimension on the charge mobility of Pb-based S-CP materials.…”
Section: Inorganic Chemistrysupporting
confidence: 52%
“…The TRMC signal or φΣμ max value, which is the product of the charge-carrier generation yield (φ) and sum of the hole and electron mobilities (Σμ), of CP1 was 2.7 × 10 –5 cm 2 V –1 s –1 , which is moderate compared to other CPs. ,, The bandgap and photoconductivity of S-based CPs has been reported to be related to the (−M–S−) n dimension . In the case of Pb-based S-CPs, remarkable photoconductivity was observed from a CP with a 2D (−Pb–S−) n layer structure . The φΣμ max value of CP1 (2.7 × 10 –5 cm 2 V –1 s –1 ) is similar to that of [Pb­( ortho -SPhOMe) 2 ] n (2.5 × 10 –5 cm 2 V –1 s –1 ) .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In prior studies, we demonstrated that most Pb(II) SÀ CPs with (À PbÀ SÀ ) n networks tend to absorb visible light. [19][20][21] In contrast, KGF-26 and KGF- [21] The absolute valence band maximum (VBM) levels were determined via photoelectron yield spectroscopy (PYS) [22] as À 6.00 eV (KGF-26) and À 5.92 eV (KGF-27) below the vacuum level (Figure S17). Considering the optical bandgap estimated by DRÀ UVÀ Vis spectroscopy, the conduction band minimum (CBM) was determined to be À 2.91 eV (KGF-26) and À 3.02 eV (KGF-27) below the vacuum level.…”
Section: Semiconductive Propertiesmentioning
confidence: 99%